FEATURES OF THE DISPOSITION OF ACTORS OF THE PHYSICAL CULTURE AND EDUCATIONAL SPACE OF THE UNIVERSITY IN THE NEW REALITY - Goncharuk, Ya.A.; Goncharuk, S.V.; Isaev, I.F.; Peresypkin, A.P. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to diagnose the dispositions of the actors in managing the development of the physical culture and educational space in universities (hereinafter referred to as the PHESU) based on the generalization of the results of the empirical sociological research "Diagnostics of the management system of the physical culture and educational space of universities" conducted in 2018-2021. Methods and structure of the study. The functioning of the PHESU and the quality of its management largely depend on the dispositions of its actors. In order to diagnose the management system for the development of the physical culture and educational space of the university, we organized a sociological study by the method of a questionnaire survey of the subjects of the federal educational institution of the Belgorod, Kursk and Lipetsk regions: student youth (n=1000), university teachers and researchers (n=300), as well as employees university administration (n=140). To solve the tasks of sociological research, a quota sample was used, which made it possible to build a micromodel of the general population - subjects of the PHESU Belgorod, Kursk, Lipetsk, Stary Oskol). Results and conclusions. It is concluded that the disposition of the actors in managing the development of the physical culture and educational space of the university, at the moment, is rightfully considered not optimal, which leads to work on their improvement.